THROTTLE DEVICE AND REFRIGERATION CYCLE APPARATUS USING THE SAME - MAEZAWA MITSUNORI; HIRASAWA YUTA (2016)
PROBLEM TO BE SOLVED: To provide a throttle device including a throttle mechanism as well as a strainer function collecting foreign matters, enabling one part to play a role of two parts, capable of reducing the number of parts, capable of realizing space saving and the saving of manufacturing processes, and contributing to improving manufacturing reliability.SOLUTION: A throttle device 1 according to an embodiment for use in a refrigeration cycle apparatus or the like comprises a strainer 3 provided within a cylindrical throttle device body 2 and collecting foreign matters. The throttle device 1 further comprises a throttle mechanism having a helical channel 5.SELECTED DRAWING: Figure 1 【課題】異物を捕集するストレーナ機能に加え、絞り機構を備え、一つの部品で二つの部品の役割を果たすことができ、部品点数を削減でき、省スペース化及び製造上の省工程化を図ることが出来、製造的な信頼性向上へも貢献する、絞り装置を提供する。【解決手段】冷凍サイクル装置等に用いられる実施形態の絞り装置１は、筒状の絞り装置本体２内部に、異物を捕集するストレーナ３を備える。また、螺旋流路５を有する絞り機構を備える。【選択図】図１